2012
DOI: 10.1177/1933719112446077
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pollutants and Female Fertility: A Systematic Review Focusing on In Vitro Fertilization Studies

Abstract: The possible adverse effects of organochlorine pollutants (OPs) on human fertility are a matter of concern. Direct evaluation of the effects on female fertility was made possible by the advent of in vitro fertilization (IVF). We conducted a systematic review to assess possible associations between OP levels and selected indicators of female fertility in the context of IVF. After harmonization, OP concentrations per unit of lipid varied considerably, OP concentrations were higher in follicular than in serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 87 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…for 7 days showed a reduction in seminal vesicle weight, serum testosterone, and dehydroepiandrosterone levels [ 10 ] while mature female rabbits exposed to dichlorodiphenyltrichloroethane (DDT) (3 mg kg −1 ) and lindane (0.8 mg kg −1 ) exhibited reduced ovulation rates [ 11 ]. Although several in-vitro studies (e.g., studies using ovarian cells) have listed the negative impacts of DDE and DDT, such as infertility and reductions in the number, development or quality of oocytes, fertilization rate, embryo quality or development, and pregnancy rate, only a few of these studies have managed to obtain statistically significant results [ 12 ]. An epidemiological study reported that high levels of serum ΣDDT (DDE + DDT) above 1 μg kg −1 were significantly correlated to low pregnancy rates in German women [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…for 7 days showed a reduction in seminal vesicle weight, serum testosterone, and dehydroepiandrosterone levels [ 10 ] while mature female rabbits exposed to dichlorodiphenyltrichloroethane (DDT) (3 mg kg −1 ) and lindane (0.8 mg kg −1 ) exhibited reduced ovulation rates [ 11 ]. Although several in-vitro studies (e.g., studies using ovarian cells) have listed the negative impacts of DDE and DDT, such as infertility and reductions in the number, development or quality of oocytes, fertilization rate, embryo quality or development, and pregnancy rate, only a few of these studies have managed to obtain statistically significant results [ 12 ]. An epidemiological study reported that high levels of serum ΣDDT (DDE + DDT) above 1 μg kg −1 were significantly correlated to low pregnancy rates in German women [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, assisted reproduction treatments have increased, including IVF. The IVF studies allow acquiring evidence on the impact of environmental pollutants on embryo quality (Kadhel et al, 2012).…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
“…The presence of DDE, MXC, or simazine (a triazine herbicide) was associated with follicular atresia (34). Given that MXC, simazine, and other pesticides (as atrazine, endosulfan, and chlordecone) are oestrogen receptor agonists (in contrast to DDE, DDT, and vinclozolin), they may have oestrogenic and/or antiandrogenic effects (5,10,35,36). This implicitly explains why some specific pesticides could be responsible for various female reproductive diseases to differing extents and why the effects of some pesticide compounds (such as DDE, PCB, and MXC) depend on the patient's genetic predisposition.…”
Section: The Association Between Pesticide Exposure and Certain Femalmentioning
confidence: 99%